Hyperuricemia in Renal patients: Treat or not to treat - Muhammad Tanzeel Abbasi Muhammad Rashid Asghar; Khuram Bashir; Muhammad Nauman Hashmi (Archives of Clinical Nephrology - Peertechz Publications, 2021)
Hyperuricemia management in chronic kidney disease is a challenging task. We encounter this dilemma on regular basis. Kidney disease patients have wide range (CKD population, Hemodialysis & peritoneal dialysis cohort and renal transplant patients).  In clinical practice wide range of opinions exists. This dubious area intrigued us to look into it. Looking into available published data majority of studies are observational and few are randomized control trials. All studies favor that high uric acid level has accelerated effect on CKD progression. Controversy is on its management, whether by treating it we are able to slow down CKD progression or not. Data supports that CKD progression is not slowed down but needs more studies to give conclusive answer. In dialysis and renal transplant patients studies showed inverse relationship of high uric levels with all-cause mortality. However, in peritoneal dialysis data suggests linear relationship of hyperuricemia with mortality.  A pro as well as anti-oxidant effect of uric acid has been discussed in literature. Variable cut off for hyperuricemia has been used but more census is on 7 mg/dl. Symptomatic gout definitely needs uric acid lowering therapy but in asymptomatic hyperuricemia no conclusion so far. There is paucity of data in maintenance dialysis and renal transplant patients.